The Ethics of Care in Barack Obama’s Speech in the United States of Women Summit - Anni Alvionita Simanjuntak; T. Thyrhaya Zein; Masdiana Lubis (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Ethics of care refers to ideas concerning the nature of morality can be judge by the Attitude. This research examines the Appraisal in Barack Obama’s speech in the United States of Women Summit by using a qualitative descriptive approach by collecting data through speech. The objectives of this research are to identify the type of Attitude and to elaborate the reason why the types of the attitude and the ethics of care are used in Obama’s speech in the United States of Women Summit. The data consisted of 113 clauses. Source of data is Obama’s speech in the United States of Women Summit that gathered from the official website. The results showed that the most dominant attitude subsystem in Obama’s speech in is appreciation, 53 clauses (47%), while there are 40 clauses (35%) categorized as judgement, and 20 clauses (18%) categorized as affect. In this case the speaker uses all positive appreciation (there is no negative appreciation category) to express his evaluation and his appreciation for the women movement and empowerment in that summit and especially the women in his country, United States of America. Furthermore, the realization types of attitude is realized the ethics of care in Obama’s speech which show his decision making about the equality of gender specially women in his administration/presidency. From the analysis, types of attitude; judgment and appreciation employ the ethics of care in valuing the personal relationship, caring attitude, and caring action. While the type of affect employs the sympathy and direct attention in doing ethics of care. As the recommendation, the researcher suggest to used ethics of care in analyze person attitude in other speeches by using appraisal, not only the attitude type but also the engagement and the graduation types.